Inclusive Education in Post-Soviet Countries: a Case of Kazakhstan - Makoelle, Tsediso Michael (NUGSE Research in Education, 3(2), 2018)
Inclusive education has become a focal point internationally (Ainscow, Dyson & Weiner, 2013). In many contexts the implementation of inclusive education is characterized by contradictions, controversies, dilemmas and anomalies (Makoelle, 2014a; Slee, 2018). The fact that inclusive education came as a critique of special education raises a lot of questions as some tend to attribute it solely to education of students with disability and special needs, while in essence it focuses on a wide spectrum of diversity such as gender, race, ethnicity, and socio-economic status (Makoelle, 2016). The emphasis on disability and special needs create a framework of thinking imbued with an extreme inclination to believe that inclusion is only about disability. The fact that there are different ways in which the notion of inclusion is conceptualized means it is enacted through different practices and policy perspectives. Whoever goes through the process of enacting inclusion, experiences it differently depending on unique situation and context (Makoelle, 2014b)...
Keywords: inclusive education; post-soviet countries